Urgensi Pendekatan Personal dalam Pembelajaran terhadap Generasi Z - Much Nuril Huda (Dinamika Pembelajaran : Jurnal Pendidikan dan bahasa, 2025)
Generation Z is the first generation to grow up entirely in a digital ecosystem. Their adaptive, visual, and hands-on experience-oriented characteristics demand innovation in learning models. This article aims to examine the urgency of implementing a personalized learning approach in modern education as a response to the learning needs of Generation Z. The research method used is a library research review of a number of scientific literature and recent research reports relevant to the characteristics and learning strategies of Gen Z. The results of the study indicate that a personalized approach can increase motivation, engagement, and learning independence by adjusting the pace and learning style, and utilizing adaptive technology based on artificial intelligence (AI). Teachers act as mentors, providing personalized guidance and building empathetic relationships with students. The conclusion of this study confirms that personalized learning is not merely a pedagogical innovation but a strategic imperative to ensure the relevance of education in the digital age.